Statistical Comparison of Cloud and Aerosol Vertical Properties between Two Eastern China Regions Based on CloudSat/CALIPSO Data - Yujun Qiu; Jing Wang; Keran Yang (Advances in Meteorology)
The relationship between cloud and aerosol properties was investigated over two 4° × 4° adjacent regions in the south (R1) and in the north (R2) in eastern China. The CloudSat/CALIPSO data were used to extract the cloud and aerosol profiles properties. The mean value of cloud occurrence probability (COP) was the highest in the mixed cloud layer (−40°C~0°C) and the lowest in the warm cloud layer (>0°C). The atmospheric humidity was more statistically relevant to COP in the warm cloud layer than aerosol condition. The differences in COP between the two regions in the mixed cloud layer and ice cloud layer (<−40°C) had good correlations with those in the aerosol extinction coefficient. A radar reflectivity factor greater than −10 dBZ occurred mainly in warm cloud layers and mixed cloud layers. A high-COP zone appeared in the above-0°C layer with cloud thicknesses of 2-3 km in both regions and in all the four seasons, but the distribution of the zonal layer in R2 was more continuous than that in R1, which was consistent with the higher aerosol optical thickness in R2 than in R1 in the above-0°C layer, indicating a positive correlation between aerosol and cloud probability.